2020
DOI: 10.1038/s12276-019-0362-8
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cell-derived exosomes: messages from dying cells

Abstract: Apoptosis, a type of programmed cell death that plays a key role in both healthy and pathological conditions, releases extracellular vesicles such as apoptotic bodies and microvesicles, but exosome release due to apoptosis is not yet commonly accepted. Here, the reports demonstrating the presence of apoptotic exosomes and their roles in inflammation and immune responses are summarized, together with a general summary of apoptosis and extracellular vesicles. In conclusion, apoptosis is not just a 'silent' type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
201
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(226 citation statements)
references
References 76 publications
6
201
0
1
Order By: Relevance
“…EVs are produced constitutively or upon activation, due to inflammation, hypoxia, oxidative stress, shear stress, senescence, cell death, exposure to bacterial endo/exotoxins, uremia, etc. [10][11][12][13][14][15]. The cargo varies depending on type and differentiation of the parent cell, microenvironmental variables, and agents that triggers EV release.…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…EVs are produced constitutively or upon activation, due to inflammation, hypoxia, oxidative stress, shear stress, senescence, cell death, exposure to bacterial endo/exotoxins, uremia, etc. [10][11][12][13][14][15]. The cargo varies depending on type and differentiation of the parent cell, microenvironmental variables, and agents that triggers EV release.…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…Apoptosis has been considered a form of 'silent' cell death for a long time, in contrast to necrosis, which frequently induces in ammation by releasing danger-associated molecular patterns (DAMPs). However, this notion has changed, and apoptosis has gradually been shown to participate in communication with neighboring cells to contribute to survival or apoptosis and remodeling of the surrounding tissues [11]. Our previous study reported that apoptotic cells in inactivated murine skin attracted macrophages (F4/80 + ) migration in in vivo transplantaion and subsequently promoted its wound healing regeneration (Le et al, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…They can comprise microvesicles (MVs), including those bearing mitochondria, as well as exosomes that are now recognized as powerful mediators of intercellular communication locally and systemically [11,12]. One advantage of MVs compared with living cells is their nanoscale size may effectively and functionally cross biological barriers, unlike synthetic drug nanocarriers and whole cells [13].…”
mentioning
confidence: 99%
“…It has been observed that EVs can be released during physiological events in vivo, such as cell growth, proliferation, activation, apoptosis, or senescence. Furthermore, some conditions, such as oxidative or shear stress, inflammation, senescence, and cell death, may also induce EV production [13][14][15][16][17][18]. In any case, EVs are released into the extracellular milieu and finally they could reach the blood circulation.…”
Section: Extracellular Vesicles Subtypesmentioning
confidence: 99%
“…Given that apoptotic cells express phosphatidylserine on their surface [35], the positivity to Annexin V (which binds phosphatidylserine) has been considered a hallmark of apoptotic bodies, even if the enrichment in caspase 3 and 7 has been proposed to be more specific for apoptotic bodies [33]. It has been recently demonstrated that, as with all the other EV subtypes, apoptotic bodies represent an active vehicle of intercellular communication from dying to living cells [14].…”
Section: Extracellular Vesicles Subtypesmentioning
confidence: 99%